The continuum of maternal sepsis severity: incidence and risk factors in a population-based cohort study. - Acosta, C; Knight, M; Lee, H; Kurinczuk, J; Gould, J; Lyndon, A (Public Library of Science, 2013)
Objective To investigate the incidence and risk factors associated with uncomplicated maternal sepsis and progression to severe sepsis in a large population-based birth cohort. Methods This retrospective cohort study used linked hospital discharge and vital statistics records data for 1,622,474 live births in California during 2005–2007. Demographic and clinical factors were adjusted using multivariable logistic regression with robust standard errors. Results 1598 mothers developed sepsis; incidence of all sepsis was 10 per 10,000 live births (95% CI = 9.4–10.3). Women had significantly increased adjusted odds (aOR) of developing sepsis if they were older (25–34 years: aOR = 1.29;$35 years: aOR = 1.41), had#high-school education (aOR = 1.63), public/no-insurance (aOR = 1.22) or a cesarean section (primary: aOR = 1.99; repeat: aOR = 1.25). 791 women progressed to severe sepsis; incidence of severe sepsis was 4.9 per 10,000 live births (95% CI = 4.5–5.2). Women had significantly increased adjusted odds of progressing to severe sepsis if they were Black (aOR = 2.09), Asian (aOR = 1.59), Hispanic (aOR = 1.42), had public/no-insurance (aOR = 1.52), delivered in hospitals with ,1,000 births/year (aOR = 1.93), were primiparous (aOR = 2.03), had a multiple birth (aOR = 3.5), diabetes (aOR = 1.47), or chronic hypertension (aOR = 8.51). Preeclampsia and postpartum hemorrhage were also significantly associated with progression to severe sepsis (aOR = 3.72; aOR = 4.18). For every cumulative factor, risk of uncomplicated sepsis increased by 25% (95% CI = 17.4–32.3) and risk of progression to severe sepsis/septic shock increased by 57% (95% CI = 40.8–74.4). Conclusions The rate of severe sepsis was approximately twice the 1991–2003 national estimate. Risk factors identified are relevant to obstetric practice given their cumulative risk effect and the apparent increase in severe sepsis incidence